Pancreatic GIST in a Patient with Limited Stage Small Cell Lung Cancer: A Case Report and Review of Published Cases. (8th August 2016) - Phan, Minh; Jones, Shari; Jenkins, Justin; Pant, Shubham; Khawandanah, Mohamad
Abstract : Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract and usually occur in the stomach and the small intestine. The pancreas is an extremely rare primary site for GISTs and there are 25 reported cases of pancreatic GIST with most being treated with surgical resection. We describe a 52-year-old African-American female who was diagnosed with limited stage small cell carcinoma in November 2009 and treated with concurrent cisplatin/etoposide chemotherapy and radiation. She subsequently achieved complete remission. Two years later she was diagnosed with localized pancreatic GIST by endoscopic ultrasonography guided fine needle aspiration. We treated her with a tyrosine kinase inhibitor (TKI) imatinib 400 mg oral dose daily as she declined surgery. Her disease is stable based on computed tomography imaging scans 40 months after diagnosis without any metastasis. To the best of our knowledge, our case is the second case of localized pancreatic GIST treated with TKI monotherapy.